Pertinence of Maize Wet Milling By-products in Ruminant Feeding-A Review - Malik, Tariq A.; Thakur, S. S.; Mahesh, M. S.; Mohini, Madhu; Tarun Kumar Varun; Mir, Shahid Hassan (International Journal of Livestock Research, 2018)
Limitation of conventional feed resources for livestock, particularly the concentrates, leaves a huge scope for the utilization of agro-industrial by-products. Maize gluten meal (MGM) and maize gluten feed (MGF) are the by-products of maize wet milling process. These are excellent feed-stuffs with practical implications in beef and dairy nutrition. The expected growth of wet milling industry in the developing countries for meeting the commercial demands of starch will increase the availability of these co-products in future. Time has arrived to recognise and utilise the feeding value of such by-products. This review aims to provide an insight into the usefulness of MGM and MGF in ruminant feeding.